LARVICIDAL ACTIVITY OF TURMERIC (CURCUMA DOMESTICA) EXTRACT AGAINST AEDES AEGYPTI L. - Indah Tri Susilowati; Tri Harningsih; Indra Ayu Vidyaningrum (Universitas Medan Area, 2021)
Indonesia occupies the top position as the country with the highest dengue cases in ASEAN. A variety of prevention dengue can be done which can be used chemicals. Chemical insecticides indeed provide effective results and optimal, but many negative impacts both on the environment and living organisms. The many negative effects of chemical insecticides led to new research in the vector control safer, simpler, and environmentally sound. Control using biological insecticides (vegetable) is one of them. One of the plants that can be used as larvicides are turmeric (Curcuma domestica). Tumeric contains bioactive compounds such as essential oils, alkaloids, flavonoids, saponins potential as an alternative killer mosquito larvae. Researchers create 6 concentration turmeric extract (0g / L; 0.25 g / L, 0.5 g / L; 1g / L; 2g / L; 4g / L) of each concentration included 25 larval Aedes aegypti L. The data obtained were performed Shapiro-Wilk normality test and then test the hypothesis by Kruskal Walis and probit test. Results obtained LC50value is 2.084g/L or 0.208% (w/v). The results showed that tumeric extract (Curcuma domestica) is effective to kill the larvae Aedes aegypti L.